STAKEHOLDERS MAPPING PENGELOLAAN WISATA TELAGA MENJER DESA MARON KECAMATAN GARUNG KABUPATEN WONOSOBO - Ratih Widya Astuti; Retno Sunu Astuti; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2023)
Menjer Lake is a natural tourist attraction located in Maron Village, Garung District, Wonosobo Regency. Compared to other tourist attractions in Wonosobo Regency, Telaga Menjer is one of the tourist attractions that experiences instability in the number of visitors each year, is less attractive to tourists, and has not been able to contribute optimally to Wonosobo Regency's PAD. The aim of this research is to identify stakeholders and their roles in the management of Menjer Lake. This research uses qualitative research methods with data collection techniques through interviews, observation and documentation. The research results show that there are 3 stakeholders involved in this management, namely the government, the private sector or business world, and the community. The Maron Village Government acts as the implementer together with the Maron Village Karang Taruna, Bumdes Sumber Lancar, Wonosobo Regency Tourism and Culture Office, and the Fishermen's Group. The role of policy creator and coordinator is carried out by the Maron Village Government, the Wonosobo Regency Tourism and Culture Office, and PT Indonesia Power. The Fishermen and Investors Group also acted as facilitators together with the Maron Village Youth Organization and the Wonosobo Regency Tourism and Culture Office. The role of the accelerator is carried out by PT Indonesia Power. Based on the power versus interest analysis, the context setter stakeholders consist of the Maron Village Government and the Wonosobo Regency Tourism and Culture Office. Players consist of Karang Taruna Maron Village, Bumdes Sumber Lancar, and PT Indonesia Power. Subjects consist of Investors and Fishermen Groups.